Nurses’ Engagement in Antimicrobial Stewardship Programmes: A Mapping Review of Influencing Factors Based on Irvine’s Theory - Susana Filipe; Paulo Santos-Costa; Celeste Bastos; Amélia Castilho (Nursing Reports)
Antimicrobial resistance (AMR) is a pressing global health challenge, driving the need for effective antimicrobial stewardship (AMS) programmes. Despite nurses’ critical role in care delivery, their involvement in AMS remains under-recognized. Objectives: This mapping review aims to identify barriers and facilitators influencing nurses’ engagement in AMS programmes and examine nursing-sensitive outcomes associated with their participation, using Irvine’s Nursing Role Effectiveness Model (NREM) as a guiding framework. Methods: A systematic mapping review was conducted following Joanna Briggs Institute (JBI) guidance and reported using the PRISMA-ScR checklist. The protocol was registered on the Open Science Framework. Searches were conducted in MEDLINE, CI-NAHL, Scopus, LILACS, Scielo, and grey literature sources. Data were extracted and categorized according to the NREM domains: structure, process, and outcomes. Results: Thirty-two studies were included. Key barriers included limited AMS knowledge, role ambiguity, hierarchical dynamics, communication gaps, and lack of standardized nursing outcomes. Facilitators encompassed targeted AMS education, participation in multidisciplinary discussions, managerial support, and defined nursing roles. Nurse-led interventions showed potential to improve infection control and antibiotic administration, although standardized outcome reporting remains scarce. Conclusions: Framed by the NREM, this review underscores the essential contribution of nurses to AMS. Addressing structural barriers, enhancing role clarity, and fostering interdisciplinary collaboration are critical to enabling nurses’ full participation. Strengthening nursing engagement in AMS not only supports effective antimicrobial use and patient safety but also reinforces health system resilience and sustainability.